2018
DOI: 10.1017/jfm.2018.882
|View full text |Cite
|
Sign up to set email alerts
|

Towards a finite-time singularity of the Navier–Stokes equations Part 1. Derivation and analysis of dynamical system

Abstract: The evolution towards a finite-time singularity of the Navier–Stokes equations for flow of an incompressible fluid of kinematic viscosity $\unicode[STIX]{x1D708}$ is studied, starting from a finite-energy configuration of two vortex rings of circulation $\pm \unicode[STIX]{x1D6E4}$ and radius $R$, symmetrically placed on two planes at angles $\pm \unicode[STIX]{x1D6FC}$ to a plane of symmetry $x=0$. The minimum separation of the vortices, $2s$, and the scale of the core cross-section, $\unicode[STIX]{x1D6FF}$,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…The result from this work shows that the high-Reynolds-number case results in smaller radii of curvature at both tipping points (namely, and mm) compared with the low-Reynolds-number case ( and mm), as illustrated in figure 9 and reported in table 4. This is as expected, as in the high-Reynolds-number case the tipping points experience more intense stretching, resulting in a higher local curvature, following the mechanism explained by Moffatt & Kimura (2019). A slight increase in curvature at tipping points is observed when the pair of tipping points approaches from far field; however, unlike what is seen in Moffatt & Kimura (2019), when tipping points are getting close enough and the bridging starts, the curvatures are flattened instead of increasing rapidly, and the vortex lines on both sides of the dividing plane tend to be more anti-parallel.…”
Section: Vortex Reconnection Dynamicssupporting
confidence: 82%
See 2 more Smart Citations
“…The result from this work shows that the high-Reynolds-number case results in smaller radii of curvature at both tipping points (namely, and mm) compared with the low-Reynolds-number case ( and mm), as illustrated in figure 9 and reported in table 4. This is as expected, as in the high-Reynolds-number case the tipping points experience more intense stretching, resulting in a higher local curvature, following the mechanism explained by Moffatt & Kimura (2019). A slight increase in curvature at tipping points is observed when the pair of tipping points approaches from far field; however, unlike what is seen in Moffatt & Kimura (2019), when tipping points are getting close enough and the bridging starts, the curvatures are flattened instead of increasing rapidly, and the vortex lines on both sides of the dividing plane tend to be more anti-parallel.…”
Section: Vortex Reconnection Dynamicssupporting
confidence: 82%
“…This is as expected, as in the high-Reynolds-number case the tipping points experience more intense stretching, resulting in a higher local curvature, following the mechanism explained by Moffatt & Kimura (2019). A slight increase in curvature at tipping points is observed when the pair of tipping points approaches from far field; however, unlike what is seen in Moffatt & Kimura (2019), when tipping points are getting close enough and the bridging starts, the curvatures are flattened instead of increasing rapidly, and the vortex lines on both sides of the dividing plane tend to be more anti-parallel. This process is depicted in figure 9( b ), where the radii of curvature reach a minimum value and then increase as the two vortex tubes approach each other.…”
Section: Vortex Reconnection Dynamicssupporting
confidence: 82%
See 1 more Smart Citation
“…Given that intense vorticity is arranged in tubes with weak curvature, additional insight could be obtained by a simple kinematic analysis of stretching generated by such structures. To this end, we consider a simple axisymmetric vortex tube with a radius of curvature R c 27 29 . Utilizing a curvilinear polar coordinate system: ( , , ), which, respectively, correspond to unit vectors in the radial direction, the azimuthal direction and the direction tangent along the (curved) axis of the tube, we assume that the vorticity is of the form .…”
Section: Resultsmentioning
confidence: 99%
“…) – which definitely breaks the local assumption required for the scaling. Inspired by the recent works of Moffatt & Kimura (2019 a , b ) on the finite time singularity of Euler and N–S equations, we studied reconnection of two colliding slender vortex rings (the ratio between the initial vortex core size and the radius of the ring is approximately 0.01) and found that before reconnection follows a scaling when (Yao & Hussain 2020 a ). The main objective of the present work is to further elucidate the time scaling of minimum separation distance for (classical) viscous vortex reconnection.…”
Section: Introductionmentioning
confidence: 99%